2012
DOI: 10.1016/j.quascirev.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Paired 26Al and 10Be exposure ages from Lundy: new evidence for the extent and timing of Devensian glaciation in the southern British Isles

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 63 publications
4
69
3
1
Order By: Relevance
“…This is consistent with recent studies demonstrating the extent of the Devensian BIIS closer offshore than previously thought (Clark et al, 2010), as confirmed through geomorphological and cosmogenic dating studies in the Scilly Isles (Scourse, 1987(Scourse, , 1991McCarroll et al, 2010) and on Lundy in the Bristol Channel (Rolfe et al, 2012). However the nearest significant upland glaciation by an independent ice mass during the LGM was in the Brecon Beacons (Wales), 150 km north.…”
Section: Glaciation and The Dartmoor Torssupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with recent studies demonstrating the extent of the Devensian BIIS closer offshore than previously thought (Clark et al, 2010), as confirmed through geomorphological and cosmogenic dating studies in the Scilly Isles (Scourse, 1987(Scourse, , 1991McCarroll et al, 2010) and on Lundy in the Bristol Channel (Rolfe et al, 2012). However the nearest significant upland glaciation by an independent ice mass during the LGM was in the Brecon Beacons (Wales), 150 km north.…”
Section: Glaciation and The Dartmoor Torssupporting
confidence: 91%
“…1). It lies well beyond the maximum limits of the British-Irish Ice Sheet (BIIS) (Fretwell et al, 2008;Clark et al, 2010;McCarroll et al, 2010;Rolfe et al, 2012). It has long been regarded as "probably the purest relict periglacial landscape in Britain" (Waters, 1960, p. 174): thus "during the Pleistocene the landscape was severely affected by periglacial processes" (Brunsden, 2007, p. 67), with extensive evidence including patterned ground, frost regolith, gelifracted outcrops and gelifluction deposits (notably 'clitter' block streams), and gentle convexo-concave slope profiles (see Campbell et al, 1998, and relevant review sections therein).…”
Section: Introduction E Dartmoor As a Tor-studded Periglacial Landscapementioning
confidence: 94%
“…In the outer Bristol Channel area, Rolfe et al . () found that glaciated granite surfaces on Lundy date to the Devensian Stage (Middle Devensian, MIS 3), indicating that they became ice‐free at that time during a phase of deglaciation. Despite the widely reported evidence of glaciation in the Bristol Channel, Carr and Hiemstra () still questioned the evidence for this in the vicinity of Lundy, although with no basis.…”
Section: Introductionmentioning
confidence: 99%
“…Sissons, ; McDougall, ). During the LGM the Lake District nourished its own ice cap, from which a radial pattern of ice dispersal developed, and contributed mass to the British Ice Sheet, which extended south to the Midlands and South Wales, and the ISIS, which extended south to the Scilly Isles (Evans et al ., ; Scourse et al ., ; McCarroll et al ., ; Rolfe et al ., ). Because Lake District valley glacier ice limits/moraines are considered to post‐date the LGM (Sissons, ; Wilson, ; Clark, ), the majority of the surface exposure ages are clearly too old and are considered to be compromised by various levels of 36 Cl inherited from a previous period of exposure (see below).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%